LTR a response to Schuh - Paul Newman (LibraryPress@UF, 1989)
Some twenty years ago Leben proposed that Hausa had a productive, essentially exceptionless P rule ("L TR") to the effect that any word fmal L L sequence automatically changed to L H if the final vowel of the word was long. Since that time, L TR has become accepted as a phonological rule of Hausa alongside such well-established rules as vowel shortening in closed syllables or palatalization of coronal consonants before front vowels. The aim of our paper was to demonstrate that there are in fact far too many counterexamples to the L TR rule to continue to accept it as a fully active synchronic rule in Hausa.